Production of xylanase intended to be used in bread-making: laboratory scale and pilot scale studies - Ongen, Gaye Ongen; Sahinbas, Dilek; Duzel, Ahmet; Duzdemir, Gizem Ezgi; Altinel, Burak; Tuluk, Kubra; Sargin, Sait (Taylor & Francis Ltd, 2024)
In this study, submerged and solid-state fermentation studies were performed for xylanase production simultaneously to determine ideal carbon and nitrogen sources together with necessary production parameters from the laboratory scale to the pilot scale. The results showed that barley malt sprout is effective as a nitrogen and a good carbon source. Under optimum conditions, xylanase activities 71.74 +/- 2.70 U/mL, 56.95 +/- 3.6 U/mL, 65.8 +/- 8 U/mL and 46.05 +/- 0.1 U/mL were achieved in shake flasks, 2, 10 and 30 L bioreactors, respectively. In solid-state fermentation studies, maximum activity in flasks was 759.15 +/- 36.16 U/g production media, and maximum activity in pilot-scale tray bioreactor productions was 1312 +/- 137.85 U/g dry substrate. Bread-making trials showed that using xylanase at 100 U/100g flour resulted in a significant increase in the loaf volume of wheat flour bread and whole wheat flour bread.
Keywords: Xylanase; Aspergillus niger; pilot scale; submerged fermentation; solid-state fermentation; bread quality